PEMETAAN POTENSI MATA AIR BERBASIS SISTEM INFORMASI GEOGRAFI (SIG) DI DAS MAROS - Alfian Hidayat; Muhammad Yusuf; Suprapta HS (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine the potential of springs in the Maros watershed by utilizing the Geographic Information System (GIS), as well as the distribution of potential springs in the Maros watershed. The parameters used are vegetation density, rainfall, topography, geology, and geohydrology. The data used is secondary data. The data analysis technique is a weighted tiered quantitative analysis by overlapping the spring potential parameter map. So that the results of the physical characteristics that determine the potential of springs in the Maros watershed are obtained, namely vegetation density with a very dense level, rainfall (3,000 - 4,000 mm/year), sloping hill topography to very steep hills and dominated by sedimentary rock types and water basins. soil. The potential level of springs in the Maros watershed in the very low potential level class is 1872.78 Ha (3%) area, then at the low hazard level class is 1505.88 Ha (2%) area, at the medium potential level class is 16257 ,6 Ha (22%), in the high potency class it was 38429.7 Ha (53%) and in the very high potency class it was 15053.7 Ha (21%).